Editorial: Obituary. Issue 3 (1st September 2015) - Wilkinson, Nicholas
Abstract : This is an 'open' issue but with a very special message in it. More than a week ago now Arch. Catalina Gandelsonas died of cancer. This sad news was relayed to me via Prof. Pat Wakely in London. Catalina was a remarkable woman. From the days at Lefke University (North Cyprus) she showed herself as a person who was very clear as to what she wanted and was most helpful and careful in achieving her aims. In the early nineties Catalina later became a member of the Open House International Board of editors. Her refereeing was always to the point with brevity. I wish to convey my condolences to her daughter and other family members and hope this message speaks for many of our other friends who also knew her. She was a remarkable person with much goodwill and a great energy and in addition to that she had a very endearing character.